Reclaiming the 'Self': self-objectification and victim-survivors' bodies in Margie Orford's The Eye of the Beholder and Akwaeke Emezi's Freshwater - Landsberg, Zoe (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
Self-objectification is conventionally viewed by objectification theorists as a negative process that is pursued by victims as a result of experiencing sexual violence. What makes self-objectification particularly negative is that it confirms that the victim feels alienated from their body following their harrowing experience. In this thesis, I argue that Margie Orford and Akwaeke Emezi depart from this view of self-objectification. Instead, through the protagonists in their respective novels, The Eye of the Beholder and Freshwater, Orford and Emezi offer a positive revision of self-objectification by articulating it as a necessary process in a victim's journey toward reclaiming their body and, with it, their concept of 'self" . To make this argument, I begin by drawing on Western existential phenomenology and African ontology to develop what is referred to as the basic relational view of the 'self' which understands the 'self' as the connection point between one's body and one's subjecthood. Applying this understanding of the 'self' to the selected texts, I show that it is the connection between each protagonist's body and spirit that is disturbed by their experience of sexual violence. Initially aligning with the negative view of self-objectification, Orford and Emezi confirm this disturbance through their protagonists' pursuits of self-objectifying behaviours. However, using Elaine Scarry's artist"“artifact model and Russel W. Belk's articulation of the 'extended self', I demonstrate that it is by means of self-objectification that the protagonists are presented as able to reestablish a meaningful connection to their violated bodies and thereby reclaim their disrupted concepts of 'self' as they journey towards survivorhood. In this way, through the victim"“survivor journeys of their respective protagonists in The Eye of the Beholder and Freshwater, Orford and Emezi inscribe the process of self-objectification with an unorthodox duality where it is not a wholly negative process, but rather one that is pivotal to a victim's survival. Thus, I conclude in this thesis, Orford and Emezi offer a positive revision of self-objectification, a revision that has not yet been studied in the scholarship on the selected primary texts.
Keywords: Self-objectification; Self in literature; Victims in literature; Detective and mystery stories -- History and criticism; Magic realism (Literature); Sex crimes in literature